The Phylogeny and Evolution of the Flashiest of the Armored Harvestmen (Arachnida: Opiliones). (5th January 2021) - Benavides, Ligia R; Pinto-da-Rocha, Ricardo; Giribet, Gonzalo
Abstract: Gonyleptoidea, largely restricted to the Neotropics, constitutes the most diverse superfamily of Opiliones and includes the largest and flashiest representatives of this arachnid order. However, the relationships among its main lineages (families and subfamilies) and the timing of their origin are not sufficiently understood to explain how this tropical clade has been able to colonize the temperate zone. Here, we used transcriptomics and divergence time dating to investigate the phylogeny of Gonyleptoidea. Our results support the monophyly of Gonyleptoidea and all of its families with more than one species represented. Resolution within Gonyleptidae s.s. is achieved for many clades, but some subfamilies are not monophyletic (Gonyleptinae, Mitobatinae, and Pachylinae), requiring taxonomic revision. Our data show evidence for one colonization of today's temperate zone early in the history of Gonyleptidae, during the Paleogene, at a time when the Neotropical area extended poleward into regions now considered temperate. This provides a possible mechanism for the colonization of the extratropics by a tropical group following the Paleocene–Eocene Thermal Maximum, explaining how latitudinal diversity gradients can be established. Taxonomic acts: Ampycidae Kury 2003 is newly ranked as family; Neosadocus Mello-Leitão is transferred to Progonyleptoidellinae (new subfamilial assignment). [Arachnids; biogeography; phylogenomics; transcriptomics.]